2016
DOI: 10.1007/s10461-016-1437-3
|View full text |Cite
|
Sign up to set email alerts
|

Online Sex-Seeking Among Men who have Sex with Men in Nigeria: Implications for Online Intervention

Abstract: The TRUST/RV368 project was undertaken to apply innovative strategies to engage Nigerian MSM into HIV care. In this analysis we evaluate characteristics of online sex-seekers from the TRUST/RV368 cohort of 1,370 MSM in Abuja and Lagos. Logistic regression and generalized estimating equation models were used to assess associations with online sex-seeking. Online sex-seeking (n=843, 61.5%) was associated with participation in MSM community activities, larger social and sexual networks, and higher levels of sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 39 publications
7
21
1
Order By: Relevance
“…We found that men who used social media for sex seeking had higher anticipated HIV stigma. This is consistent with a Nigerian study showing that online sex-seeking was associated with the higher stigma of same-sex behavior (39). A few reasons might explain the connection between anticipated HIV stigma and sex-seeking on social media.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that men who used social media for sex seeking had higher anticipated HIV stigma. This is consistent with a Nigerian study showing that online sex-seeking was associated with the higher stigma of same-sex behavior (39). A few reasons might explain the connection between anticipated HIV stigma and sex-seeking on social media.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, community-based organizations have increasingly launched gayfriendly medical service programs, so MSM could disclose their sexuality and concerns regarding HIV more easily when facing a gay-friendly medical provider (48). In response, those medical providers could be a source of social support and would be more likely to offer accurate and targeted HIV knowledge and decrease the fear and stigma towards HIV among MSM (39).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, community-based organizations have increasingly launched gayfriendly medical service programs, so MSM could disclose their sexuality and concerns regarding HIV more easily when facing a gay-friendly medical provider (43). In response, those medical providers could be a source of social support and would be more likely to offer accurate and targeted HIV knowledge and decrease the fear and stigma towards HIV among MSM (36).…”
Section: Association Between Anticipated Hiv Stigma and Behavioral Vamentioning
confidence: 99%
“…[17][18][19] In areas where smartphone usage is less prevalent, there are other webbased venues to meet sex partners, such as Facebook groups, Manhunt or Planet Romeo. 20 For MSM in particular, online social networking has made meeting sexual partners during travel increasingly feasible. For example, among MSM attending a gay pride event in Denver, Colorado, 12% of men interviewed sought sexual partners online before travel.…”
Section: Increasing Access To Sex Partners During Travel Through Onlimentioning
confidence: 99%
“…This is important, because MSM who seek sex partners through online platforms are more likely to report engaging in CAI and having multiple sexual partnerships, as well as being less likely to know the HIV status of these partners, compared with those who meet their partners offline. 7,20,26 A meta-analysis of 11 observational studies found the odds of CAI were higher in online-initiated sexual encounters compared with sexual partnerships conducted offline among MSM, suggesting that online platforms make partner identification for CAI easier. 26 This relationship may be explained by the ease in which sexual partners can be identified, especially for those willing to engage in high-risk sexual behaviours like CAI with a partner of unknown HIV-status or unknown viral load suppression status.…”
Section: Increasing Access To Sex Partners During Travel Through Onlimentioning
confidence: 99%